Use the le'vy Model on stock returns for some Iraqi banks estimate - حمود, مناف يوسف; موسى, مريم جمعة (Journal of Economics and Administrative Sciences, 2016)
In this article we  study a single stochastic process model for the evaluate the assets pricing and stock.,On of the models le'vy . depending on the so –called Brownian subordinate as it has been depending on the so-called Normal Inverse Gaussian (NIG). this article aims as the estimate that the parameters of his model using my way (MME,MLE) and then employ those  estimate of the parameters is the study of stock returns and evaluate asset pricing for both the united Bank and Bank of North which their data were taken from the Iraq stock Exchange. which showed the results to a preference MLE on MME based on the standard of comparison the average square error (MSE) .and the yield  rate of the stock of the Bank United is higher than the rate of returns for the North Bank as well as the United owning  less coefficient c.v  compared  with the North Bank   and both estimater (MME,MLE) .therefore the United Bank is the best investment of the Northa Bank  in addition , the North Bank was less efficient than the  United Bank for, leading this speech to preference of investors to invest with united Bank and its superiority on the North Bank.